Perspektif Muhammad Sa‘Îd Al-Asymâwî tentang Historisitas Syari’ah - Mutawalli Mutawalli (Ulumuna, 2009)
The Islamic law in Islamic thought tradition is viewed as significant knowledge for development of other Islamic knowledge. However, in an epistemological area, the concept of Islamic law provokes debates in terms of its implementation, for example, whether it is considered syarî‘ah or fiqh? Such question is always raised by contemporary Muslim thinkers like Muhammad Sa‘îd al-Asymâwî. Al-Asymâwî’s question is related to his paradigm that firmly differentiates syarî‘ah (Islamic law) as religious teachings and fiqh (religious thoughts). Syarî‘ah is Allah’s ways and methods consisting of values and principles that are flexible following community movement. While fiqh is Muslim scholars’ deduction, exploration and interpretation of Al-Qur’an and Sunnah, it is limited to times and spaces. Consequently, according to such paradigm, some Islamic orders that are considered authoritative by the majority of Muslim scholars should be reviewed such as Islamic inheritance, criminal and political laws. With this approach, Al-Asymâwî is claimed as a real guard of liberalism and secularism among Muslim thinkers.